The Effect of Sharia and Religiosity Labels on Community Interests Using Sharia Banking (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This research is motivated by the problems that the researchers found,  which there are still many Muslim communities in Pontianak city prefer to use  conventional banks rather than sharia banks. The lack of interest in the Muslim  community to use syaria banks is due to many factors including the sharia label  and religiosity. This study aims to determine the effect of the sharia label and  religiosity on people's interest in using Islamic banks. The sample size in this study  uses the Lemeshow formula, this was because the population size was unknown.  The data used in this study were primary data obtained through questionnaires  distributed to the Muslim community in Pontianak City in 2023. Based on a sample  of 100 respondents using multiple linear regression analysis, the results of this  study indicated that the label sharia and religiosity have a positive effect and giving  significance to the interest in becoming a customer of sharia banks. The results of  this study also showed that the Sharia Label and Religiosity have a simultaneous  effect on Public Interest in Using Sharia Banks.